(untitled) (International Seven Journal of Health Research, 2023)
Introduction: A high number of students linked to the health area have been related to problems with poor sleep quality, raising an alert about the need to promote programs to improve the duration and quality of the night rest hours of pharmacy, nursing and physiotherapy students. Objective: To analyze the sleep quality of Nursing, Pharmacy and Physiotherapy students enrolled in the night shift of UNEC - Nanuque Campus. Methodology: The present research went through the theoretical assumptions of a quantitative research, of exploratory and descriptive character, in which it sought in an educational institution, the perceptions of 70 students enrolled in UNEC - Nanuque Campus, through a questionnaire containing 10 structured questions. Results: About 95% of respondents sleep after 23 hours, 72% take more than half an hour to sleep, 74% sleep less than recommended by the medical association, 51% rate the quality of and 70% said they have already ingested medicine to induce sleep. Conclusion: The picture of few hours of sleep, justified the excessive use of self-medication and the search for sleeping pills, something worrying because using medications on their own can be harmful to the students’ bodies.